Environmental Baseline Survey and Assessment for DrillingCutting Disposal in Makasar Strait: Effect on plankton and benthos communities - , Tjut Sugandawaty Djohan ([Yogyakarta] : TOTAL E&P INDONESIE and Center for Environmental S, 2004)
Cutting disposal waste is a one primary concern during exploration and development of oil operation. The objective of this study was to determine the baseline environmental conditions of the proposed disposal locations and extrapolate the impacts of drill&nbsp